2003
DOI: 10.1210/me.2001-0210
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Liver X Receptors in Lipid Accumulation in Adipocytes

Abstract: The pivotal role of liver X receptors (LXRs) in the metabolic conversion of cholesterol to bile acids in mice is well established. More recently, the LXRalpha promoter has been shown to be under tight regulation by peroxisome proliferator-activated receptors (PPARs), implying a role for LXRalpha in mediating the interplay between cholesterol and fatty acid metabolism. We have studied the role of LXR in fat cells and demonstrate that LXR is regulated during adipogenesis and augments fat accumulation in mature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
141
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 65 publications
20
141
5
Order By: Relevance
“…In addition, and most importantly, silencing LXR expression totally eliminates the response of the endogenous adipocyte apoE gene to PPAR␥ stimulation. Consistent with the observations of others (14,15), treatment of adipocytes with PPAR␥ agonists increases both total cellular and nuclear LXR protein. It is of interest that, despite this increase in LXR protein, the response of the apoE gene to the combined addition of a PPAR␥ and LXR agonist is not greater than that to either agonist alone.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, and most importantly, silencing LXR expression totally eliminates the response of the endogenous adipocyte apoE gene to PPAR␥ stimulation. Consistent with the observations of others (14,15), treatment of adipocytes with PPAR␥ agonists increases both total cellular and nuclear LXR protein. It is of interest that, despite this increase in LXR protein, the response of the apoE gene to the combined addition of a PPAR␥ and LXR agonist is not greater than that to either agonist alone.…”
Section: Discussionsupporting
confidence: 91%
“…Sterol efflux from differentiating adipocytes remains very limited despite induction of ABCA1 and apoE expression during adipocyte differentiation (19). Furthermore, treatment of adipocytes with LXR agonists, which stimulate apoE and ABCA1 expression, increases adipocyte lipid accumulation (15). We have shown that adipocyte apoE is required for optimal TG accumulation in adipocytes (6).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, this enhancer contains a conserved functional LXR response element. Because the expression of LXR␣ is positively regulated by PPAR␥ agonists in adipocytes (42)(43)(44)(45), this LXR element, in the presence of an endogenously generated ligand, could account for increased apoE gene expression in response to ciglitazone. On the other hand, a functional PPAR␥ response element has also been identified for transducing the apoE gene response to ciglitazone in U87MG astrocytoma cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…First, NR1HRα and β are abundantly produced in adipocytes, preferentially in subcutaneous rather than in visceral white adipose tissue [9]. In addition, NR1HR production is regulated by the key adipocyte transcription factor PPARγ either in macrophages and in adipose tissue, and many NR1HR target genes are also highly expressed in adipocytes [10][11][12]. Moreover, ligand activation of NR1HR regulates production of the insulin-responsive glucose transporter solute carrier family 2 (facilitated glucose transporter), member 4 (SLC2A4, formerly known as GLUT4) both in vivo and in murine and human adipocytes, through direct interaction with a conserved NR1HR response element in the Slc2a4 promoter.…”
Section: Introductionmentioning
confidence: 99%